Investigating the Effects of Different Sources and Levels of Zinc, Copper, Manganese, and Iron on the Performance, Blood Parameters, and Tibia Characteristics of Broiler Chickens During the Grower and Finisher Periods - Ali Tayebi pour; Reza Majidzadeh Heravi; Hasan Kermanshahi (پژوهشهای علوم دامی ایران)
Introduction: Insufficient minerals play a crucial role in various physiological functions such as digestive, and metabolic processes within the body. They act as cofactors in many enzymes and serve as catalysts in enzyme systems. These substances also contribute to the immune system and hormone secretion pathways (Tom et al., 2003). Zinc, copper, manganese, and iron are micro-elements that play essential roles in the growth, development, bone tissue formation, and immunity of broiler chickens (Echeverry et al., 2016; M'Sadeq et al., 2018). Zinc acts as an antioxidant, protecting cell membranes against peroxidation (Olivares et al., 2007). It also exhibits synergistic effects with vitamin E and polyphenols (Wołonciej et al., 2016). Copper is vital for growth, enzyme activity, and reproduction. It plays a significant role in various enzyme activities, such as ceruloplasmin, cytochrome oxidase, and superoxide dismutase, which help protect cells against oxidative stress (Hussein and Staufenbiel, 2012). Iron interacts with other elements, particularly copper, acting as a catalyst in oxidation reactions (Wołonciej et al., 2016). Manganese is also crucial for fetal growth, body weight gain, bone growth, and reproduction (Olgun, 2017).Materials and Methods: To investigate the impact of different sources and levels of zinc, copper, manganese, and iron on the performance, blood parameters, and tibia characteristics of broiler chickens during the grower and finisher periods, 1250 broiler chickens from the Ross 308 strain were divided into 10 experimental treatments. Each treatment consisted of 5 replicates with 25 observations in a completely randomized design. The experimental treatments included mineral elements (zinc, copper, manganese, iron) from two organic and inorganic sources at levels of 40, 60, 80, 100, and 120% of the requirements during the grower and finisher periods. Blood samples were collected from two chicks in each replicate at 42 days of age and analyzed for various parameters at the laboratory of Razavi Hospital in Mashhad.Results and Discussion: The effects of different levels of organic and inorganic minerals (zinc, copper, manganese, iron) on the performance of Ross 308 broiler chickens during the grower, finisher, and entire experimental periods are presented in Table 2. The results indicated significant effects of different treatments on body weight gain, feed consumption, and feed conversion ratio across all periods. The highest body weight gain during the grower period was observed in groups receiving 120%, 100%, and 80% of organic mineral requirements and 120% of inorganic requirements. Daily feed consumption was highest in the group receiving 40% of inorganic and organic mineral requirements and lowest in groups receiving 80%, 100%, and 120% of inorganic and 60%, 80%, 100%, and 120% of organic requirements. The feed conversion ratio was significantly higher in groups receiving 40% of organic and inorganic requirements compared to other groups during the grower period. In the finisher period, the highest daily body weight gain was observed in groups receiving 120%, 100%, 80% of organic mineral requirements and 120%, 100% of inorganic mineral requirements. Daily feed consumption was significantly lower in groups receiving 100%, 120% of inorganic mineral requirements and 120%, 100%, 80%, 60% of organic requirements during the finisher period. Throughout the rearing period (11-42 days), daily body weight gain was significantly higher in groups receiving 120%, 100% of organic mineral requirements and 120% of inorganic mineral requirements. Daily feed consumption was highest in the group receiving 40%, 60% of mineral requirements from inorganic sources.Conclusion: The study results demonstrate that different sources and levels of recommended mineral requirements have significant effects on performance, bone mineral storage, and bone physical properties. The lowest feed conversion ratio during the entire rearing period was observed in groups receiving 80%, 100%, and 120% of the requirements from organic and mineral sources. Daily weight gain was significantly higher in groups receiving 100%, 120% of the recommended requirements of organic minerals compared to other groups. Zinc, copper, manganese, and iron stored in bones were significantly higher in groups receiving 80%, 100%, 120% of the recommended requirements of organic minerals and 100%, 120% of the recommended inorganic requirements. Fracture energy was significantly higher in groups receiving 120%, 100%, 80% organic and inorganic minerals. Based on the findings, it is recommended to use 80% of minerals in organic form due to its high storage capacity in the tibia bone and its ability to achieve performance similar to 100% and 120% of the requirements from organic and inorganic sources.